Can Birds Get Lost? - Myers, Jack; Nang ChanYeema (New York, USA Boyds Mills Press, 1991)
Dr. Jack Myers answers questions posed by children about animals. Many questions taken from columns in Highlights for Children.
Keywords: Juvenile Nonfiction